Evaluation of HBx Antigen in Patients with Chronic Hepatitis B Virus Infection (Iraqi Journal of Medical Sciences, 2021)
Background: Hepatitis B virus (HBV) is a serious public health problem worldwide and major cause of chronic hepatitis, cirrhosis, and hepatocellular carcinoma (HCC).Objective: To assess the association of the role hepatitis B x antigen (HBxAg) in chronic HBV; active and inactive patients, and complicated patients.Methods: Ninety blood samples from patients who had chronic HBV were enrolled in this study. Serum samples were screened by enzyme linked immunosorbent assay (ELISA) technique for the detection of HBxAg. Viral nucleic acid was extracted from these 90 samples, and plasma HBV viral load was investigated by real time-polymerase chain reaction (RT-PCR).Results: The overall prevalence of HBxAg was 26.7% with a significantly higher prevalence in active than inactive patients.Conclusion: The high HBxAg prevalence rates in active chronic patients raise the possibility of increasing risk of disease progression.Keywords: Hepatitis B virus (HBV), hepatitis B X antigen (HBxAg), hepatocellular carcinoma (HCC)Citation: Mahdi AF, Al-Khezrachi AH, Shamran HA, Al-Obaidi AB. Evaluation of HBx antigen in patients with chronic hepatitis B virus infection. Iraqi JMS. 2021; 19(1): 18-23. doi: 10.22578/IJMS.19.1.3
Keywords: Hepatitis B virus HBV; hepatitis B X antigen HBxAg; hepatocellular carcinoma HCC